1998
DOI: 10.1364/ao.37.002464
|View full text |Cite
|
Sign up to set email alerts
|

Practical model for the calculation of multiply scattered lidar returns

Abstract: An equation to predict the intensity of the multiply scattered lidar return is presented. Both the scattering cross section and the scattering phase function can be specified as a function of range. This equation applies when the cloud particles are larger than the lidar wavelength. This approximation considers photon trajectories with multiple small-angle forward-scattering events and one large-angle scattering that directs the photon back toward the receiver. Comparisons with Monte Carlo simulations, exact d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
162
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(169 citation statements)
references
References 19 publications
4
162
1
2
Order By: Relevance
“…Each of this population is parameterized in the model. This model has been compared to Eloranta's model (Eloranta, 1998) for a wide range of cloud profiles and lidar parameters and found that reproduces the high-order Eloranta calculation when the latter takes into account 5th or 6th order scattering (Hogan, 2006). This model was also used by Seifert et al (2007) to estimate the contribution of multiple scattering effects to the effective optical properties of cirrus clouds during Indian Ocean Experiment (INDOEX).…”
Section: Multiple Scattering Effectmentioning
confidence: 99%
“…Each of this population is parameterized in the model. This model has been compared to Eloranta's model (Eloranta, 1998) for a wide range of cloud profiles and lidar parameters and found that reproduces the high-order Eloranta calculation when the latter takes into account 5th or 6th order scattering (Hogan, 2006). This model was also used by Seifert et al (2007) to estimate the contribution of multiple scattering effects to the effective optical properties of cirrus clouds during Indian Ocean Experiment (INDOEX).…”
Section: Multiple Scattering Effectmentioning
confidence: 99%
“…This effect depends on factors including laser penetration depth, cloud range and height, the field-of-view of the receiver, particle size distribution and shape (Eloranta, 1998;Hogan and Illingworth, 2003). Sassen and Comstock (2001) assumed a multiple scattering factor η of 0.9 for subvisible cirrus clouds, of 0.8 for relatively thick clouds and 0.6 to 0.7 for optically thick clouds.…”
Section: Ohp Ground-based Lidarmentioning
confidence: 99%
“…The selected time windows for lidar analysis are in the range 15 -45 minutes, while the used effective vertical resolutions are in the range 160-350 m. These resolutions have been optimized in a way to obtain lidar profiles at the highest vertical resolution with a random uncertainty lower than 30%. The profiles of extinction coefficient with clouds are corrected for multiple scattering [3,4].…”
Section: Methodsmentioning
confidence: 99%